Analysis of Frailty Syndrome in Elderly Farmers - TA Larasati; L. Ristia Eiska (Faculty of Medicine, Public Health, and Nursing, 2023)
Background: Lampung with a high population of farmers has entered with an old population. That inpacted Increasing age on several health problems, one of which is Frailty Syndrome / geriatric syndrome. This study aims to determine sociodemographic aspects, family functions, marital status, educational status, psychology, cognitive, and sleep quality on frailty syndrome. Methods: The research used an analytic observation method and a cross-sectional approach. Pusposive cluster sampling technique. This research was conducted in 7 villages in Muara Sungkai sub-district, North Lampung district, on 77 elderly farmers with the inclusion criteria agreed to the informed consent, aged >60 years, and did not have a disability. Frailty Syndrome based on the FRAIL-J instrument. Family function was assessed from Smilkstein's Family System APGAR Items, Cognitive function based on MMSE (Mini Mental State Examination) instrument, Psychological based on GDS (Geriatric Depression Scale) instrument and Sleep Quality based on Pittsburgh Sleep Quality Index (PSQI). Results: The results showed that there were 80.5% old farmers with Frailty Syndrome and 19.5% experienced pre-frailty. Variables related to frailty syndrome were age (p=0.014 ; 95% CI = 0.013 – 0.871), Family Function (p= <0.01 ; 95% CI = 2.998 – 28.038) , Educational Status (p=0.008; CI 95 % = 1.164-29.353) and sleep quality (p=0.033 ; 95% CI = 1.133-11.154) had a significant relationship with Frailty Syndrome. Conclusion: Age, family function, educational status and sleep quality are significantly associated with frailty syndrome.